6p-12=-8+7p

Simple and best practice solution for 6p-12=-8+7p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-12=-8+7p equation:


Simplifying
6p + -12 = -8 + 7p

Reorder the terms:
-12 + 6p = -8 + 7p

Solving
-12 + 6p = -8 + 7p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-7p' to each side of the equation.
-12 + 6p + -7p = -8 + 7p + -7p

Combine like terms: 6p + -7p = -1p
-12 + -1p = -8 + 7p + -7p

Combine like terms: 7p + -7p = 0
-12 + -1p = -8 + 0
-12 + -1p = -8

Add '12' to each side of the equation.
-12 + 12 + -1p = -8 + 12

Combine like terms: -12 + 12 = 0
0 + -1p = -8 + 12
-1p = -8 + 12

Combine like terms: -8 + 12 = 4
-1p = 4

Divide each side by '-1'.
p = -4

Simplifying
p = -4

See similar equations:

| 8(7p-6)= | | 4s-8=8+8s | | (4b+3)(b-12)= | | -35=-7x+7 | | 5m^2+2=m | | 4/5y+7=47 | | 15-4x=23 | | -28/7/20=c | | 18=-36+9y | | 2.6+y=2y+8.6 | | -2(X-3)=5X-8 | | 3/5-2/3x=29 | | (6x)2= | | -5(5+2x)=-105 | | -56=7w+56 | | -296=-6x-7(4x-16) | | 3(2t-5)+4t= | | -7/14=c | | 165=30n+5 | | (33b-5)-8(4b+4)=-2 | | -88=11s-99 | | .5x^2+2x+3=x+7 | | -2.4/1.2=c | | 8.95+1.50n=26.95 | | 99=11x+y | | 41=-7x+2(-4x-32) | | -54=-9a-27 | | p=g+5u | | 8(2a-3)=-104 | | 8p+8q= | | .5x^2+2x=3x+7 | | a/6x=5x |

Equations solver categories